The effect of a combined exercise program on the fatigue severity of patients with breast cancer undergoing chemotherapy: A randomized clinical trial study - Elahe Darvishi; Amir Musarezaie; Masoud Bahrami; Jahangir Karimian (Wolters Kluwer Medknow Publications, 2023)
Background: Breast Cancer (BC) is one of the most common cancers in the world, including in Iran. Chemotherapy as one of the basic treatments for BC leads to many side effects such as fatigue. This study aimed to examine the effect of a combined exercise program on the intensity of fatigue in patients with BC undergoing chemotherapy. Materials and Methods: This clinical trial study was conducted on 64 patients with BC undergoing chemotherapy referring to the Seyyed al-Shoada and the Al-Zahra clinics from January to April 2022. Eligible patients who met inclusion criteria were recruited by the convenience sampling and then assigned randomly to intervention and control groups. The combined exercise program in the intervention group was done for 8 weeks as three sessions a week (34 sessions) each for 35-40 min. Piper's Fatigue Scale was completed for both groups before and after the intervention. Data were analyzed using descriptive and inferential statistical methods. Results: The results showed that the mean score of fatigue intensity in both control and intervention groups had a statistically significant difference after the intervention (p = 0.004). The mean fatigue intensity score in the intervention group decreased significantly from mean (SD) 8.17 (1.88) to 5.56 (1.74). Conclusions: Based on the results, a combined exercise program can reduce fatigue in patients with BC. Therefore, nurses can utilize exercise programs and practices as a subset of complementary medicine alongside other treatment methods, which can effectively promote cancer patients' quality of life by reducing their fatigue.